Доктрина Пінкертона в кримінальному праві США:критичний огляд та перспективи вдосконалення - Полянський, Євген Юрійович; Полянский, Евгений Юрьевич; Poljanskij, Evgenij (My University, 2011)
The author applies to specific features of Pinkerton doctrine — a concept of imputed liability for conspirators, arisen from judicial case. According to the concept, the conspirators are liable for all consequences caused by criminal activity regardless to personal guiltiness and personal contribution. Such approach engenders controversy in science, and in fact — needs revision.
Полянський Є. Ю. Доктрина Пінкертона в кримінальному праві США:критичний огляд та перспективи вдосконалення / Є. Ю. Полянський // Наукові праці Національного університету «Одеська юридична академія». Т. 10 / голов. ред. С. В. Ківалов ; МОНмолодьспорт України, НУ "ОЮА". – Одеса : Юрид. л-ра, 2011. – C. 218-226.
Keywords: кримінальне право США; відповідальність співучасників; об'єктивне ставлення у вину; уголовное право США; ответственность соучастников; объективное вменение; US Criminal Law; responsible partners; objective imputation